IMPLEMENTASI MEDIA AR BERMUATAN KEARIFAN LOKAL LAMPUNG PADA MATERI GEOMETRI: PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Jeshinta Dwi Cahyani; Fitria Lestari; Noprisa Noprisa (Mandalika Mathematics and Educations Journal, 2026)
The development of digital technology encourages the use of innovative learning media such as Augmented Reality (AR) to transform abstract Mathematics concepts into more concrete and contextual. This study aims to measure the improvement of students' mathematical communication skills through the implementation of AR media based on Lampung local wisdom on limas and prism materials. This study uses a quantitative approach with a pre-experimental design of one group pretest–posttest involving 15 grade VIII students of Assafina Junior High School Bandar Lampung. Data were collected through tests, questionnaires, and documentation, with test instruments in the form of five description questions that met the criteria of validity and reliability with a Cronbach's Alpha coefficient of 0.99. Data analysis was carried out using Shapiro–Wilk test, paired sample t−test, and N−Gain. The results showed an increase in students' average scores from 51 to 76.73 with a significance level of less than 0.05 and an N−Gain value of 0.51 which was included in the medium category. In addition, students' responses to the use of media reached 87.85% which was classified as very practical. These findings show that AR media based on local wisdom is effective in supporting the development of students' mathematical communication through visual, symbolic, and verbal representations in spatial geometry learning.